2014
DOI: 10.1017/s1744133114000152
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the smoking response to health shocks by out-of-pocket spending risk

Abstract: An existing literature demonstrates that adverse changes to health can lead to improvements in health behaviors. Although the exact explanations for these empirical findings are debated, some posit that individuals learn about their true health risks through health shocks. Updated health risk information can then induce changes in health behaviors. While we follow a learning framework, we argue that past work has neglected the role of health insurance and medically related financial risk within this decision m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 56 publications
1
11
1
Order By: Relevance
“…To explore heterogeneity in the smoking response, we focus on the degree of financial risk exposure to medical spending at the time of disease onset. Our preceding conceptual framework views self‐protection (i.e., smoking cessation) and market insurance as at least partial substitutes for a given smoker – consistent with other economics studies (Dave and Kaestner, ; De Preux, ; Ehrlich and Becker, ; Rashad and Markowitz, ; Richards and Helmchen, ; Richards and Marti, ). While health risk beliefs after a health shock could be similarly updated across insurance groups, the signal in the financial domain is likely stronger for individuals with less coverage.…”
Section: Methodssupporting
confidence: 78%
See 4 more Smart Citations
“…To explore heterogeneity in the smoking response, we focus on the degree of financial risk exposure to medical spending at the time of disease onset. Our preceding conceptual framework views self‐protection (i.e., smoking cessation) and market insurance as at least partial substitutes for a given smoker – consistent with other economics studies (Dave and Kaestner, ; De Preux, ; Ehrlich and Becker, ; Rashad and Markowitz, ; Richards and Helmchen, ; Richards and Marti, ). While health risk beliefs after a health shock could be similarly updated across insurance groups, the signal in the financial domain is likely stronger for individuals with less coverage.…”
Section: Methodssupporting
confidence: 78%
“…The estimates in Table also indicated that NSR health problems could lead to higher medical expenditures but then failed to display any corresponding relationship with smoking behavior for either insurance group. Furthermore, Richards and Marti's () study finds a similar pattern of results among non‐US health care systems that typically establish OOP maximums for individuals – effectively eliminating the possibility of catastrophic losses and thereby large income effects. Our data also only encompass older adults, who are unlikely to be experiencing their first financial shock over the course of their smoking lifetimes.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations